Synthesis of 7-epi-Goniodiol by Proline-Catalyzed Diastereoselective Direct Aldol Reaction - Veena, Bacchu; Sharma, Gangavaram V. M. (Synlett, 2014)
A simple organocatalytic approach was developed for the total synthesis of 7-epi-goniodiol. The strategy involves l-proline-catalyzed diastereoselective direct aldol reaction and Baeyer–Villiger oxidation as key steps for the construction of chiral lactone.
Keywords: styryllactones; 7-epi-goniodiol; proline; aldol reaction; Baeyer–Villiger oxidation